2018
DOI: 10.1111/jofi.12602
|View full text |Cite
|
Sign up to set email alerts
|

Homeowner Borrowing and Housing Collateral: New Evidence from Expiring Price Controls

Abstract: I empirically analyze how changes in access to housing collateral affect homeowner borrowing behavior. To isolate the role of collateral constraints from that of wealth effects, I exploit the fully anticipated expiration of resale price controls on owner‐occupied housing in Montgomery County, Maryland. I estimate a marginal propensity to borrow out of housing collateral that ranges between $0.04 and $0.13 and is correlated with homeowners' initial leverage. Additional analysis of residential investment and ex‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…The two papers closest to our work are DeFusco (2018) and Benmelech, Guren, and Melzer (2023). DeFusco (2018) finds that relaxing collateral constraints on homeowners leads to an increase in borrowing and also applications for home improvement permits.…”
Section: Related Literaturementioning
confidence: 71%
“…The two papers closest to our work are DeFusco (2018) and Benmelech, Guren, and Melzer (2023). DeFusco (2018) finds that relaxing collateral constraints on homeowners leads to an increase in borrowing and also applications for home improvement permits.…”
Section: Related Literaturementioning
confidence: 71%
“…Secondly, since the real estate can be used as mortgage, high housing price increases the market value of a house so that the family could obtain more low-interest loans through mortgaging their house to financial sector. The financial constraint is thus alleviated and the family can smooth their consumption [16,[26][27][28].…”
Section: High House Prices and Consumptionmentioning
confidence: 99%
“…Oikarinen (2009) and DeFusco (2018) found that rising housing prices increase the expected wealth of households, leading to more consumption and ultimately expanding credit demand. Due to the rise in house prices, it is common for a Chinese family to buy a house with a loan [50,51]. Higher house prices naturally lead to an increase in housing loans.…”
Section: Theoretical Analysismentioning
confidence: 99%